Pemberdayaan Anak-anak Rumah Asuh Baiti Jannati melalui Pelatihan Pembuatan Yogurt dan Penguatan Kemampuan Literasi - Puspawiningtiyas, Endar; Hawanti, Santhy Hawanti; Purwanto, Lahan Adi; Sya'diyah, Siti Khalimatus; Fauzy, Reza Fahmi; Aisyah, Nur (Darmabakti : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
The low literacy rates among foster children and the financial viability of Baiti Jannati Home for Foster Children are issues. Through literacy-promoting initiatives and yogurt production training, the service seeks to improve partners' financial independence and literacy levels. Five steps will make up the implementation strategy: problem identification, training, implementation, monitoring, and evaluation. The findings demonstrated the development of a reading corner and a sustainable literacy model, the diversification of four flavor options, and improved yogurt production skills (average post-test score of 87.9). The ability of partners to make and package their own yogurt as well as the development of children's literacy skills are results of this activity. Foster families' role as social empowerment agents has been strengthened, and foster children's economic and intellectual readiness has increased thanks to the program. Through interdisciplinary humanitarian projects, the outputs help higher education achieve key performance indicators.